Evaluation of Chromogenic Media for Detection of Methicillin-Resistant Staphylococcus aureus - Malhotra-Kumar, Surbhi (American Society for Microbiology (ASM), 2010)
Rapid laboratory diagnosis is critical for treating, managing, and preventing methicillin-resistant Staphylococcus aureus (MRSA) infections. We evaluated and compared the potential for MRSA detection of five chromogenic media, Brilliance MRSA agar (Oxoid), ChromID (bioMérieux), MRSASelect (Bio-Rad), CHROMagar (CHROMagar Microbiology), and BBL-CHROMagar (BD Diagnostics). Media were tested with log serial dilutions (10(0) to 10(6) CFU) of pure isolates of MRSA (n = 60), non-MRSA (n = 27), and defined mixtures thereof simulating clinical samples (n = 84). Further evaluations were done on pre-enriched nasal and groin screening swabs (n = 213) from 165 hospitalized patients. Randomized samples were spiral plated on each medium and independently scored by five investigators for characteristic colonies at 24 and 48 h of incubation. Confirmatory testing of up to five putative MRSA colonies recovered from each medium was done. The cumulative average sensitivity with isolates, mixtures, and clinical samples was the highest for Brilliance MRSA agar (97%) and similar for the other four media (≥92%). The cumulative average specificity was the highest for BBL-CHROMagar (99%), followed by MRSASelect (98%), CHROMagar (97%), ChromID (89%), and Brilliance MRSA agar (86%). All of the media detected MRSA at 10 and 1 CFU, although at these low loads, few MRSA samples harboring SCCmec type III or IV were misinterpreted as non-MRSA by investigators. False-positive results were mainly due to methicillin-resistant S. epidermidis. For an arbitrary MRSA prevalence of 5% and based on patient sample evaluations, the positive predictive values for BBL-CHROMagar and CHROMagar (∼84%) were the highest. The negative predictive values of all of the media were ≥92% for MRSA prevalences ranging from 5% to 30%. In conclusion, BBL-CHROMagar and CHROMagar gave the best overall results for detection of MRSA, irrespective of the sample concentration, investigator, or incubation period.